2012
DOI: 10.1175/jcli-d-11-00295.1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Diurnal Variation of Tropical Convection Simulated by a Global Nonhydrostatic Model without Cumulus Parameterization

Abstract: This study investigated the resolution dependence of diurnal variation in tropical convective systems represented by a global nonhydrostatic model without cumulus parameterization. This paper describes the detailed characteristics of diurnal variation in surface precipitation based on three-dimensional data, with the aim of explicitly clarifying the mechanism that underlies the variation. The study particularly focused on the evolution in the size of the precipitation area for deep convective systems with an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 50 publications
4
32
0
Order By: Relevance
“…The precipitation peaks appear around 2400 LST in Δ14 and Δ7. Previous studies using NICAM (Sato et al 2009;Noda et al 2012) also reported a midnight peak of precipitation at these resolutions. The peak time changes to around 2000 LST in Δ3.5.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…The precipitation peaks appear around 2400 LST in Δ14 and Δ7. Previous studies using NICAM (Sato et al 2009;Noda et al 2012) also reported a midnight peak of precipitation at these resolutions. The peak time changes to around 2000 LST in Δ3.5.…”
Section: Resultsmentioning
confidence: 56%
“…Global simulations with 14 km and 7 km grid spacing without CP schemes have effectively reproduced the diurnal precipitation cycle in tropical regions (Sato et al 2009;Noda et al 2012;Kodama et al 2015), especially over the ocean. Nevertheless, the precipitation peak in the diurnal cycle over land occurs later than in TRMM observations.…”
Section: Introductionmentioning
confidence: 99%
“…The configuration of the nonhydrostatic icosahedral atmospheric model, (NICAM) (Tomita and Satoh 2004;Satoh et al 2008Satoh et al , 2014 used in this study was the same as that described by Noda et al (2012). Cloud microphysics processes were computed using a one-moment scheme that predicts the mixing ratios of rainwater, graupel, and snow and also diagnoses cloud water and cloud ice (Tomita 2008).…”
Section: Modelmentioning
confidence: 99%
“…For CTL, the SST boundary conditions and sea ice concentrations (SICs) were the same as those used in the boreal summer 2004 experiment of Noda et al (2012). The conditions for GW were developed using the dataset of the World Climate Research Program Coupled Model Inter-comparison Project phase 3 (CMIP3) and the method of Mizuta et al (2008).…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation